1973
DOI: 10.1149/1.2403424
|View full text |Cite|
|
Sign up to set email alerts
|

Solvent Equilibria of AlCl[sub 3]-NaCl Melts

Abstract: The solvent acid‐base properties of AlCl3‐normalNaCl melts containing 50–70 mole per cent AlCl3 at temperatures of 175°–355°C are fully described by the use of three equilibrium constants 2AlCl3)(1=Al2Cl6)(1 Knormalo AlCl4−+AlCl3=Al2Cl7− K2 2AlCl4−=Al2Cl7−+Cl− KM At 175°C the K values on the mole fraction scale are 2.86×107,2.4×104,normaland 1.06×10−7 , respectively. The ΔH and ΔS values for each equilibrium were found to be temperature independent and calculated values for previously unreported formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
1
2

Year Published

1973
1973
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(90 citation statements)
references
References 11 publications
2
85
1
2
Order By: Relevance
“…The parameters shown in Table 1 given by Boxall et al [16] were used to determine equilibrium [21] (27)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters shown in Table 1 given by Boxall et al [16] were used to determine equilibrium [21] (27)…”
Section: Resultsmentioning
confidence: 99%
“…The electrolyte is a molten AlC1 3 -NaCl salt saturated with NaCl and can be treated as a concentrated mixture of Na +, A1Cl 4 and Cl [ 16] .…”
Section: Model Developmentmentioning
confidence: 99%
“…The necessary equilibrium formation constant Ks was found much too high (six order of magnitude) with respect to what is expected by extrapolation at room temperature of K2 constants known for inorganic chloroaluminates (3). Another explanation involves the fact that the exact formulation of the emf is given by (33) II tA I ( ... ) [9] In the preceding calculations, only the first term is taken into account.…”
Section: Resultsmentioning
confidence: 82%
“…Another explanation involves the fact that the exact formulation of the emf is given by (33) II tA I ( ... ) [9] In the preceding calculations, only the first term is taken into account. For titration curves involving inorganic chloroaluminate, it has been generally accepted that either the last two terms are indeed negligible (2,3) or can be calculated based on the assumption that the cation is the only current carrying species (4) 9 In agreement with the work by King and,~ye (33), for room temperature organic chloroaluminate melts, the organic cation cannot be considered with certainty as the only current carrying species because of its much larger size with respect to the inorganic cation 9 By measuring conductivities of various molten methylpyridinium halides, Newman et al concluded that the principal charge carrier is the anion simply because chloride melts are better conductors than bromide melts. However, such a simple conclusion cannot be made when comparing the conductivities of several alkylpyridinium halides where both the alkyl chain and the halide were changed (29).…”
Section: Resultsmentioning
confidence: 99%
“…The concentration overvoltage corresponds to the reversible cell potential of the following concentration cell A1/NaC1-A1C13(jNaC1-A1C13cb~/A1 where subscripts (s) and (b) indicate the surface and bulk concentrations of both aluminum-containing species and sodium chloride, respectively. Such a cell should exhibit a cell potential corresponding to electrode reaction [1] such as (17) R…”
Section: Discussionmentioning
confidence: 99%